Biomarker and Pollen Evidence for Late Pleistocene Pluvials in the Mojave Desert. Issue 10 (17th October 2022) - Peaple, Mark D.; Bhattacharya, Tripti; Lowenstein, Tim K.; McGee, David; Olson, Kristian J.; Stroup, Justin S.; Tierney, Jessica E.; Feakins, Sarah J.
Abstract: The climate of the southwestern North America has experienced profound changes between wet and dry phases over the past 200 Kyr. To better constrain the timing, magnitude, and paleoenvironmental impacts of these changes in hydroclimate, we conducted a multiproxy biomarker study from samples collected from a new 77 m sediment core (SLAPP‐SRLS17) drilled in Searles Lake, California. Here, we use biomarkers and pollen to reconstruct vegetation, lake conditions, and climate. We find that δD values of long chain n‐ alkanes are dominated by glacial to interglacial changes that match nearby Devils Hole calcite δ 18 O variability, suggesting both archives predominantly reflect precipitation isotopes. However, precipitation isotopes do not simply covary with evidence for wet‐dry changes in vegetation and lake conditions, indicating a partial disconnect between large scale atmospheric circulation tracked by precipitation isotopes and landscape moisture availability. Increased crenarchaeol production and decreased evidence for methane cycling reveal a 10 Kyr interval of a fresh, productive, and well‐mixed lake during Termination II, corroborating evidence for a paleolake highstand from shorelines and spillover deposits in downstream Panamint Basin and Death Valley during the end of the penultimate (Tahoe) glacial (140–130 ka). At the same time brGDGTs yield the lowest temperature estimates (mean months above freezing = 9°C ± 3°C) of the 200 Kyr record. These limnological conditions are not replicated elsewhere in the 200 Kyr record, suggesting that the Heinrich stadial 11 highstand was wetter than the last glacial maximum and Heinrich 1 (18–15 ka). Plain Language Summary: Searles Valley in the Mojave Desert, California, contains a saltpan, the remnants of a former lake. Shoreline features show that the former lake was at times 274 m deep. We studied the ancient lake mud and salt deposits below the valley floor to a depth of 77 m in a sediment core drilled in 2017. The remains of microbes and plants allow us to reconstruct past climate conditions. We find that during cooler glacial periods, conifer forests covered the landscape and plant wax in the core records rainfall that is chemically different from today. These differences are similarly recorded in nearby cave deposits, suggesting changing storm tracks. The wettest climates were found in the cool climate of the penultimate glacial (about 135, 000 years ago) when Searles Lake vigorously overflowed into Panamint Basin and Death Valley. Key Points: Biomarker and pollen record from Searles Lake, CA sediment core spanning 200 Kyr Changes in plant wax hydrogen isotopes consistent with regional speleothems Archaeal lipids reveal lake highstands, Termination 2 wetter than Termination 1